PENGETAHUAN DAN SIKAP IBU TERHADAP TUMBUH KEMBANG BAYI USIA 6-18 BULAN DI UPT PUSKESMAS BANGKO JAYA KABUPATEN ROKAN HILIR - Nurul Halimah; Yesi Septinawati; Rizka Mardiya; Hirza Rahmita (Ensiklopedia Research and Community Service Review, 2026)
Infancy aged 6–18 months is a critical period in child growth and development and is strongly influenced by the mother’s role as the primary caregiver. Mothers’ knowledge and attitudes play an important role in providing stimulation, monitoring growth, and early detection of developmental problems. This study aimed to determine the relationship between mothers’ knowledge and attitudes and the growth and development of infants aged 6–18 months at the Bangko Jaya Primary Health Center, Rokan Hilir Regency. This study used a quantitative design with a cross-sectional approach. The population consisted of all mothers with infants aged 6–18 months, with a total sample of 32 respondents selected using a total sampling technique. Data were collected using questionnaires to assess mothers’ knowledge and attitudes and the Pre-Screening Developmental Questionnaire (KPSP) to assess infant growth and development. Univariate and bivariate analyses were performed. The results showed that most mothers had good knowledge (53.1%), sufficient knowledge (21.9%), and poor knowledge (25.0%). Positive attitudes were found in 46.9% of mothers, while 53.1% had negative attitudes. Most infants had normal growth and development (68.8%), while 31.2% showed abnormal development. Bivariate analysis revealed a significant relationship between mothers’ knowledge and infant growth and development (p = 0.001) and between mothers’ attitudes and infant growth and development (p = 0.000). In conclusion, mothers’ knowledge and attitudes are significantly associated with the growth and development of infants aged 6–18 months. Therefore, strengthening maternal health education through counseling and routine monitoring is recommended.Keyword : Mothers’ knowledge, Mothers’ attitudes, Infant growth and development, Infants aged 6–18 months